2021
DOI: 10.1111/ajt.16503
|View full text |Cite
|
Sign up to set email alerts
|

Natural influenza infection produces a greater diversity of humoral responses than vaccination in immunosuppressed transplant recipients

Abstract: The humoral immune response to influenza virus infection is complex and may be different compared to the antibody response elicited by vaccination. We analyzed the breadth of IgG and IgA responses in solid organ transplant (SOT) recipients to a diverse collection of 86 influenza antigens elicited by natural influenza A virus (IAV) infection or by vaccination. Antibody levels were quantified using a custom antigen microarray. A total of 120 patients were included: 80 IAV infected (40 A/H1N1 and 40 A/H3N2) and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Current subunit vaccine strategies to optimize T cell responses to influenza challenge are mostly directed towards the most mutable proteins such as Haemagglutinin and Neuraminidase. There is evidence to suggest that HLA-I restricted T cell responses are more directed towards the more highly conserved internal viral proteins, whereas humoral responses are dominated by envelope proteins [ 43 ]. Despite the proteome of influenza comprising of only a dozen proteins, this yields many thousands of potential T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Current subunit vaccine strategies to optimize T cell responses to influenza challenge are mostly directed towards the most mutable proteins such as Haemagglutinin and Neuraminidase. There is evidence to suggest that HLA-I restricted T cell responses are more directed towards the more highly conserved internal viral proteins, whereas humoral responses are dominated by envelope proteins [ 43 ]. Despite the proteome of influenza comprising of only a dozen proteins, this yields many thousands of potential T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Natural infection with influenza virus in patients with transplants resulted in stronger Ab responses with a greater variety than vaccination with a split virus vaccine [ 248 ]. It has also been shown that booster vaccinations provide additional immunogenic protection in recipients of solid organ transplants [ 249 ].…”
Section: Immunocompromised Individualsmentioning
confidence: 99%
“…Although studies have shown beneficial effects from high doses and booster vaccinations, at the current moment the main recommendation for immunocompromised populations is to receive the annual inactivated influenza vaccine at the standard single dose [ 240 ]. There are different methods that are being researched to improve vaccine immunogenicity in immunocompromised individuals by addition of adjuvants, such as MF59 or increasing vaccine dosages [ 248 , 260 ].…”
Section: Immunocompromised Individualsmentioning
confidence: 99%
“…There is evidence to suggest that HLA-I restricted T cell responses are more directed towards the more highly conserved internal viral proteins, whereas humoral responses are dominated by envelope proteins [39]. Despite the proteome of influenza comprising of only a dozen proteins, this yields many thousands of potential T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%